A methodology for evaluating social impact of Environmental Education master training program - Mola López , Enrique Loret; Méndez Santos , Isidro Eduardo (Transformación, 2024)
The paper is intended to describe a methodology for evaluating social impact of Environmental Education master training program by presenting its main stages. The framework serving as starting point and other empirical methods lead to systematized and define the terms of environmental professional training, professional performance of the environmental educator, evaluation, evaluation of professional performance of environmental educators and impact evaluation; as well as distinguishing the functions of impact evaluation in the postgraduate program favoring professor, tutors and trainees development. Previously appraised by consulting experts who gave it high ranks, this methodology is currently being used in evaluating second and third editions.
Keywords: environmental professional training; professional performance of environmental educator; impact evaluation; evaluation; evaluation of professional performance of environmental educator